AsÄlÄ«b Taâ€™lÄ«m Al-Lughah Al-â€˜Arabiyah Li-Ghairi Al-NÄá¹iqÄ«n BihÄ - Mokhtari, Hadjer (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This article topic is about the common strategies of teaching Arabic to non-native speakers, where language teaching began from the ancient era until our time now, due to the old contactÂ Â  of the non-Arabs, their language and their culture with the Arabs, the level of education rose first to preserve the Arab language and heritage from disappearance and distortion.Â  Then the foreigners' interest in him through the ages, this prompted Arab scholars to devote their efforts and develop ways to teach it as a second language to non-native speakers. And thatâ€™s because teaching Arabic requires great experience and effort, and complete knowledge, in order to learn and teach it, and this is what will be presented below.ÙŠØµØ¨ Ù…ÙˆØ¶ÙˆØ¹ Ù‡Ø°Ø§ Ø§Ù„Ù…Ù‚Ø§Ù„ ØÙˆÙ„ Ù…Ø¬Ù…Ù„ Ø§Ù„Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ø§Ù„Ø´Ø§Ø¦Ø¹Ø© Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„Ù‘ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ ØŒ ØÙŠØ« Ø£Ù†Ù‘Â  ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„Ù‘ØºØ© Ø¨Ø¯Ø£ Ù…Ù†Ø° Ø§Ù„Ø¹ØµØ± Ø§Ù„Ù‚Ø¯ÙŠÙ… ØØªÙ‰ Ø¹ØµØ±Ù†Ø§ Ø§Ù„Ù…Ø¹Ø§ØµØ± Ù‡Ø°Ø§ ÙˆÙ†Ø¸Ø±Ø§ Ù„Ù„Ø§ØØªÙƒØ§Ùƒ Ø§Ù„Ø°ÙŠ ÙƒØ§Ù† Ù‚Ø¯ÙŠÙ…Ø§ Ù…Ù† Ø·Ø±Ù Ø§Ù„Ø£Ø¹Ø§Ø¬Ù… ÙˆÙ„ØºØªÙ‡Ù… ÙˆØ«Ù‚Ø§ÙØªÙ‡Ù… Ù…Ø¹ Ø§Ù„Ø¹Ø±Ø¨ØŒ Ø§Ø±ØªÙØ¹ Ù…Ø³ØªÙˆÙ‰ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø£ÙˆÙ„Ø§ Ù„Ù„ØÙØ§Ø¸ Ø¹Ù„Ù‰ Ø§Ù„Ù„ØºØ© ÙˆØ§Ù„Ù…ÙˆØ±ÙˆØ« Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù…Ù† Ø§Ù„ØªØØ±ÙŠÙ ÙˆØ§Ù„Ø²ÙˆØ§Ù„ ÙˆØ§Ù„ØªØ´ÙˆÙŠÙ‡ØŒ Ø«Ù… Ø¨Ø¹Ø¯ Ø°Ù„Ùƒ Ø¥Ù‡ØªÙ…Ø§Ù… Ø§Ù„Ø£Ø¹Ø§Ø¬Ù… Ø¨Ù‡ Ø¹Ø¨Ø± Ø§Ù„Ø¹ØµÙˆØ±ØŒ Ù…Ø§ Ø¯ÙØ¹ Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ø¹Ø±Ø¨ Ù„ØªÙƒØ±ÙŠØ³ Ø¬Ù‡ÙˆØ¯Ù‡Ù… ÙÙŠÙ‡Ø§ ÙˆÙˆØ¶Ø¹ Ø·Ø±Ù‚ Ù„ØªØ¯Ø±ÙŠØ³Ù‡Ø§ ÙƒÙ„Ù‘ØºØ© ØªØ§Ù†ÙŠØ© Ù„ØºÙŠØ± Ù†Ø§Ø·Ù‚ÙŠÙ‡Ø§ØŒ Ø§Ø° Ø£Ù†Ù‘ ØªØ¯Ø±ÙŠØ³Ù‡Ø§ ÙŠØªØ·Ù„Ø¨ Ø®Ø¨Ø±Ø© ÙˆØ¬Ù‡Ø¯Ø§ ÙƒØ¨ÙŠØ±ÙŠÙ† ÙˆØ¥Ù„Ù…Ø§Ù…Ø§ ÙƒÙ„Ù‘ÙŠØ§ Ø¨Ø§Ù„Ù„Ù‘ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø£Ø¬Ù„ Ø§Ù„ØªÙ…ÙƒÙ† Ù…Ù†Ù‡Ø§ Ùˆ Ø§Ù„ØªÙ…ÙƒÙ† Ù…Ù† ØªØ¹Ù„ÙŠÙ…Ù‡Ø§.